A passively harmonically mode-locked soliton erbium-doped fiber laser with low pumping threshold using a single-walled carbon nanotubes - Rosdin, R.Z.R.; Ali, N.M.; Arof, Hamzah; Harun, Sulaiman Wadi (John Wiley & Sons, 2015)
We demonstrate a passively harmonically mode-locked soliton Erbium-doped fiber laser (EDFL) with low pumping threshold using single-walled carbon nanotubes (SWCNTs) embedded in poly ethylene oxide (PEO) thin film as a passive saturable absorber. The film with a thickness of 50 m was fabricated using a prepared homogeneous SWCNT solution with 0.1 loading percentage, which was mixed with a diluted PEO solution and casted onto a glass petri dish to form a thin film by evaporation technique. The film is sandwiched between two fiber connectors to construct a saturable absorber, which is then integrated in an EDFL cavity to generate a stable passive mode-locking of a soliton laser operating at 1560 nm at the 4th, 7th, and 15th harmonic of fundamental cavity frequency when the pump powers of 1480 nm laser diode are 14.9, 17.5, and 20.1 mW, respectively. The 4th harmonic pulses are characterized in detail with a repetition rate of 44.84 MHz, a transform-limited pulse width of 1.19 ps, side-mode suppression ratio of larger than 20 dB and pulse energy of 9.14 pJ. (c) 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:799-803, 2015